Formulasi Sediaan Nano Herbal Tempuyung (Sonchus arvensis L.) dalam Bentuk Self Nano-Emulsifying Drug Delivery System (SNEDDS) - Budy Wijiyanto; Primadara Damayanti; Mira Amaliasari Sitorus; Ratih Dyah Listianingrum; Arifa Caryn Dea; Yandi Syukri (Fakultas Farmasi Universitas Andalas, 2016)
Tempuyung (Sonchus arvensis L.) is a plant native to Indonesia with a diuretic and antioxidant effect. To obtain the optimal therapeutic effect need innovation to make it the nano herbs preparations. This research aims to preparation and characterization of nano herbal tempuyung in the form of Nano Self-emulsifying Drug Delivery System (SNEDDS). The active substance of tempuyung was extracted with ethanol and the solvent evaporated to obtain a viscous extract. Extracts were standardized following the Indonesian Pharmacopeia Herbal. Next, the SNEDDS of tempuyung were made using Capryol-90 as oils, tween 20 as surfactants and PEG 400 as co-surfactant. SNEDDS was characterized include particle size and zeta potential. The viscous extract obtained from extraction was 77.52 g. This result has been eligible if compared with Indonesian Pharmacopoeia Herbal that mentions the acquisition of thick leaf extract tempuyung yield is not less than 7.5%. Tempuyung formulation in dosage forms SNEDDS obtained a clear nanoemulsion with a particle size of 16.2 ± 1.06 nm and zeta potential value of -37.48 ± 0.74 mV. It can be concluded that the tempuyung extract can produce a nano herbs in SNEDDS preparation.